Historical Analysis of Climate Variability and Agricultural Production in Nigeria (1931-2020) - Alexander Chinago Budnukaeku; Ojule Soldier Emmanuel (Journal of World Economy, 2024)
This study investigates the historical dynamics of climate variability and its impacts on agricultural production in Nigeria from 1931 to 2020. Utilizing a robust analytical framework that integrates climatic data analysis, statistical modelling, and geographic information system (GIS) techniques, the research explores trends in temperature and precipitation across different agro-ecological zones. Key findings reveal a consistent upward trend in average annual temperatures, with more pronounced warming observed in northern Nigeria, notably the Sahelian zone. Concurrently, precipitation patterns exhibit regional disparities, characterized by increased rainfall in southern regions and variable patterns in the north, including periods of severe droughts during the 1970s and 1980s. Statistical analyses employing Mann-Kendall trend tests and regression models confirm significant temperature increases and varying precipitation trends, underscoring their direct impacts on agricultural productivity. The study highlights the sensitivity of crop yields to climatic factors, demonstrating that rising temperatures adversely affect staple crops such as maize, millet, and sorghum, while adequate precipitation plays a critical role in enhancing yields. Socio-economic factors, including disparities in resource access between northern and southern regions, influence farmers’ adaptive capacity and resilience to climate variability. Adaptation strategies adopted by Nigerian farmers, such as adjusted planting schedules, crop diversification, and irrigation practices, are explored within the context of socio-economic constraints and infrastructural limitations. Spatial analysis using GIS provides insights into the differential impacts of climate variability across Nigeria, emphasizing the vulnerability of northern regions to climate shocks compared to the relative resilience of southern regions. Policy implications underscore the urgency of promoting climate-resilient agricultural practices, improving resource access, enhancing rural infrastructure, and implementing targeted capacity-building initiatives. These measures are essential for enhancing adaptive capacity, resilience, and sustainable agricultural development amidst on going climate variability and change in Nigeria.